2002
DOI: 10.1073/pnas.132195699
|View full text |Cite
|
Sign up to set email alerts
|

Mutually regulated expression of Pax6 and Six3 and its implications for the Pax6 haploinsufficient lens phenotype

Abstract: Pax6 is a key regulator of eye development in vertebrates and invertebrates, and heterozygous loss-of-function mutations of the mouse Pax6 gene result in the Small eye phenotype, in which a small lens is a constant feature. To provide an understanding of the mechanisms underlying this haploinsufficient phenotype, we evaluated in Pax6 heterozygous mice the effects of reduced Pax6 gene dosage on the activity of other transcription factors regulating eye formation. We found that Six3 expression was specifically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 47 publications
6
74
1
Order By: Relevance
“…Members of the Six family have been implicated in the proliferation of pluripotent precursor cells during development (3,(5)(6)(7)(8)(9)(10). Loss-of-function of Six1 in mice results in a reduction in size or the absence of various organs, because of a decrease in proliferation and an increase in apoptosis (6-8, 39, 40).…”
Section: Six1 Induces Cellular Proliferation and Increases Tumor Volumentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the Six family have been implicated in the proliferation of pluripotent precursor cells during development (3,(5)(6)(7)(8)(9)(10). Loss-of-function of Six1 in mice results in a reduction in size or the absence of various organs, because of a decrease in proliferation and an increase in apoptosis (6-8, 39, 40).…”
Section: Six1 Induces Cellular Proliferation and Increases Tumor Volumentioning
confidence: 99%
“…The Six family of homeobox genes has been implicated in the proliferation of progenitor populations before cell type specification (3)(4)(5)(6)(7)(8)(9)(10). Six6 represses the cyclin-dependent kinase inhibitor p27, thereby promoting progenitor cell proliferation in the pituitary gland and the retina (3).…”
mentioning
confidence: 99%
“…There is evidence that the expression of c-Maf(62) and Six3 (75) is regulated by Pax6 and that Pax6 is able to form specific complexes with both factors. (76,77) Moreover, Pax6 itself may be such a target gene, as there are autoregulative mechanisms of Pax6 gene transcription, which are mediated by Pax6-binding sites in the Pax6 promoter (78) and/or the distal tissue-preferred 3′-enhancer of the Pax6 gene (75,79) The fact that Pax6 is able to form complexes with other homeodomain-containing proteins such as Six3(77) raises the distinct possibility that Pax6 might form similar complexes with itself. Such Pax6-Pax6 complexes might be critically required for activating the transcription of some selected target genes, but might be less available or difficult to assemble under conditions of haploinsufficiency.…”
Section: Molecular Mechanisms Of Pax6 Haploinsufficiencymentioning
confidence: 99%
“…These data suggest that Six-3, along with Pax-6, is also at the top of the hierarchy of genes that is responsible for lens induction. Indeed, it has been shown that Six-3 and Pax-6 can mutually activate one another through binding sites in their respective enhancer elements [50].…”
Section: Six-3mentioning
confidence: 99%